Bronchodilation by an inhaled VPAC2 receptor agonist in patients with stable asthma. Issue 3 (1st March 2003) - Lindén, A; Hansson, L; Andersson, A; Palmqvist, M; Arvidsson, P; Löfdahl, C-G; Larsson, P; Lötvall, J
Abstract : Background: The synthetic vasoactive intestinal peptide (VIP) analogue Ro 25-1553 is a selective VIP-PACAP type 2 (VPAC2 ) receptor agonist that causes a bronchodilatory effect in guinea pigs in vivo. The effect of Ro 25-1553 given by inhalation to patients with asthma was studied and compared with that of a long acting β2 adrenoceptor agonist. Methods: Twenty four patients with moderate stable asthma participated in a double blind, randomised, placebo controlled, crossover study. The primary variable was bronchodilatory effect (increase in forced expiratory volume in 1 second, FEV1 ) after inhalation of Ro 25-1553 (100 μg or 600 μg) and formoterol (4.5 μg), respectively. Putative side effects were characterised by monitoring sitting blood pressure, serum potassium, electrocardiography and echocardiography. Results: Inhalation of 600 μg Ro 25-1553 caused a rapid bronchodilatory effect (geometric mean increase in FEV1 compared with placebo) within 3 minutes of 6% (95% CI 4 to 9), as did inhalation of formoterol (8% (95% CI 5 to 10)). The corresponding maximum bronchodilatory effect during 24 hours was similar for 600 μg Ro 25-1553 (7% (95% CI 4 to 10)) and the reference bronchodilator formoterol (10% (95% CI 7 to 12)). However, for both doses of Ro 25-1553 the bronchodilatory effect was attenuated 5 hours after inhalation whereas formoterol still had a bronchodilatory effect 12 hours after inhalation. Neither Ro 25-1553 nor formoterol produced any clinically relevant side effects. No drug related difference in adverse events was observed. Conclusion: Inhalation of a synthetic selective VPAC2 receptor agonist constitutes a promising approach for bronchodilation in patients with asthma.